Study of Fisheries Subsector in Supporting Regional Development in Sibolga: Studi Peran Subsektor Perikanan dalam Pengembangan Wilayah di Kota Sibolga - Panggabean, Muhammad Aspan (Jurnal Ilmu Tanah dan Lingkungan, 2016)
Fisheries subsector is expected to be a strategic sector for future regional development in Sibolga, because this sector is a fundamental resource and has renewable character. The purposes of the study are to (1) identify the fisheries subsector development in Sibolga, (2) analyze the backward and forward linkages of the fisheries subsector economy in Sibolga, (3) explore the perceptions of stakeholders about fisheries subsector development in Sibolga, and (4) formulate the direction of fisheries subsector development priorities in Sibolga. The data analysis used is descriptive analysis, Analytical Hierarchy Process (AHP), and Input-Output (I-O). The results show that the fisheries subsector contributes to the highest gross regional domestic product up to 22.86% and contributes to the total output up to 17.70%. Fisheries still have the potential to explore 123.63 thousand tons in WPP-572 zones, in addition to the exploitation outside the exclusive economic zone. The aquaculture activities (KJA) still have space 1, 276.97 ha to be utilized, located in the district of North Sibolga and Sibolga City. Fisheries subsector in total still has small backward and forward linkage. The low linkages fisheries subsectors provide a low impact on increasing the output of other sectors either direct and indirect linkages to other sectors. The perception of all stakeholders says human resources from fishing activities is a top priority in developing the fisheries subsector, but from the analysis, human resource aquaculture should be apriority development in fisheries subsector in Sibolga. Keywords: Fisheries subsector, linkages, regional development, Sibolga